Optimalisasi Emotional Awareness dan Emotional Regulation melalui Media Emotional Jar di SDN Bataan 2 Bondowoso - M. Reza Hafid Al Faris; Farah Salsabila Hakim; Riskiyah Putri; Najcha Aisyah; Sofi Aprilia; Putri Dwi Andita; Riebie Frieska Ayu Dewi; Nova Shufia Tahmida; Agung Nugroho Puspito (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
The ability to recognize and manage emotions is an important aspect in the social and emotional development of elementary school students. This activity aims to optimize students' emotional awareness and emotional regulation through emotional jar media. The activity was carried out on 15 students in grades IV and V using participatory methods through lectures, interactive discussions, game-based learning, simulations, and evaluation through pre-tests and post-tests. There was an increase in understanding when implementing the Emotional Jar media. The results showed an increase in student understanding of all materials provided. Understanding of recognizing emotions increased by 63%, Understanding of the causes of emotions increased by 69%, understanding of how to manage emotions increased by 75%. These findings indicate that the Emotional Jar media is effective for use as a social emotional learning tool to help students understand, reflect on, and manage emotions well.